2013
DOI: 10.1016/j.ijporl.2013.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Internet and smartphone use by parents of children attending a pediatric otolaryngology service

Abstract: CitationPatterns of Internet and smartphone use by parents of children attending a pediatric otolaryngology service. Objectives: To assess Internet use and the influence of smartphones on health-information seeking by parents and carers of children with ENT conditions. Methods: A paper-based questionnaire was circulated to parents attending otolaryngology services in both the out-patient and day-case settings at a tertiary referral centre. Results: 79.5% of questionnaires were returned. 29.9% had consulted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 22 publications
2
39
0
Order By: Relevance
“…We analyzed the use and diffusion of MED among young radiation oncologists, but it is worthwhile to note that a consistent literature has also been produced studying the potential impact of MED on educational processes of medical students and in the informational background of patients. [17][18][19][20][21][22][23] In this context, the importance of a correct knowledge of the clinical use of apps is strongly needed and should be underlined. [23][24][25][26] Indeed, the important potential advantages could be mitigated by some critical issues that must be strictly taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the use and diffusion of MED among young radiation oncologists, but it is worthwhile to note that a consistent literature has also been produced studying the potential impact of MED on educational processes of medical students and in the informational background of patients. [17][18][19][20][21][22][23] In this context, the importance of a correct knowledge of the clinical use of apps is strongly needed and should be underlined. [23][24][25][26] Indeed, the important potential advantages could be mitigated by some critical issues that must be strictly taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, historically underserved groups such as African Americans and Latinos have comparable, if not higher, cell phone usage compared with the general population (Smith, ). Research also indicates high parental acceptance of technology‐based interventions to enhance children's use of primary care (Hoffstetter, Vargas, Kennedy, Kitayama, & Stockwell, ), specialist care (Glynn, O'Duffy, O'Dwyer, Colreavy, & Rowley, ), and community supports specific to CSHCN (Parette, Meadan, Doubet, & Hess, ). Yet only one study in this review investigated a technology‐based intervention (Swallow et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the many challenges, there has been an increase in consumer acceptance of health apps [37], including apps for maternal and child health. A recent US study found most parents were willing to use an app with information regarding their child's ear nose and throat (ENT) problem [38]. In the UK, there have been two reported cases of parents presenting to the emergency department with their babies because apps they were using to monitor development highlighted potential problems [14].…”
Section: Discussionmentioning
confidence: 99%